Exploring the hadron gas phase of relativistic heavy-ion collisions at the LHC - Agrawal Neelima (EPJ Web of Conferences, 2024)
The lifetimes of hadronic resonances are comparable to the one of the hadron gas phase created in the late stages of high-energy nuclear collisions. Therefore, a significant fraction of resonances decay inside a high-density medium and their decay daughters rescatter with nearby hadrons destroying their initial kinematic correlations. The competing effect of resonance regeneration via pseudo-elastic interactions of hadrons interplays between the rescattering effect, modifying the measured yields and transverse-momentum spectra of hadronic resonances. These effects are studied by measuring the production yield ratio of resonances to the corresponding long-lived particle as a function of the hadronic lifetime, i.e. charged-particle multiplicity. In addition, measurements of the differential yields of resonances with different masses, quark content, and quantum numbers help in understanding particle production mechanisms, strangeness production, and parton energy loss. This article reports recent ALICE measurements on resonances and the use of the experimental input in a partial chemical equilibrium-based thermal model to constrain the kinetic freezeout temperature. This is a novel procedure that is independent of assumptions on the flow velocity profile and the freeze-out hypersurface.